The postal history of the Antarctic, 1904–49 - Bagshawe, Richard W.; Goldup, John (Polar Record, 1951)
The philatelic effusion of a desolate region is due to various causes—frequently political, often financial, sometimes philatelic, but rarely postal. It is therefore hardly surprising that the Antarctic should have produced a variety of material for the philatelist. Post offices have been established by governments in support of claims and counter-claims, by expeditions to help finance themselves, and even by individuals eager to obtain souvenirs; postal facilities have also been provided for men engaged in whaling and scientific work; in addition, there are many stamps which depict antarctic motifs suitable for inclusion in an antarctic “subject” collection. Selectively collected, philatelic material in these categories is of great interest and offers abundant variety and range.